Meta-Analisis: Pengaruh Soal HOTS terhadap Kemandirian Santri dan Pengembangan Panca Jiwa Pondok selama Ujian Muroja'ah Ammah di Pondok Pesantren Darunna'im - Aminudin, Aminudin; Baihaqi, Wazin; Hilmiyati, Fitri; Wasehudin, Wasehudin (FONDATIA, 2024)
This study aims to evaluate the impact of implementing HOTS questions on the independence of students and the development of Panca Jiwa at Darunna'im Islamic Boarding School during the Ujian Muroja'ah Ammah. Historically, students have focused on religious studies, but this has now expanded to include cognitive, affective, and psychomotor abilities. HOTS questions play a significant role in the educational process because they test beyond memorization and require complex problem-solving skills. This research uses meta-analysis data from 20 national and international journals published between 2015 and 2021 to measure the influence of HOTS on student abilities. The findings show that participation in HOTS questions increases student independence by 45.70% and develops Panca Jiwa by 35.19%, with an effect size of 2.01, which is considered high. These results indicate that the implementation of HOTS questions in the curriculum significantly affects student independence and the development of Panca Jiwa in the Darunna'im Islamic Boarding School environment during the Ujian Muroja'ah Ammah in Cirende Kalanganyar, Lebak, Banten.